Properties of the Drugs Used for Virechana Karma-A Review - Unnikrishnan, R G (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda, or ancient Indian medicine, is based on ancient writings and takes a comprehensive approach to both mental and physical well-being. Ayurvedic medicine is one of the world’s oldest medical systems and is still used in traditional health care in India. Ayurveda advocates the use of Shodhana and Shamana to treat various illnesses. Virechana karma (purgation) is included under Panchakarmas or five purificatory methods. Virechana karma is the process of removing doshas from the body through the Adhobhaga (lower orifice). It helps with health promotion in addition to helping to eliminate doshas (humours). Virechana and other purification techniques are necessary before initiating Rasayana therapy (rejuvenation). The effect of Virechana may be so strong, according to Kashyapasamhita, that it may improve the quality of Beeja or sperm and ovum. The classics identify several medications with the ability to cause Virechana. Ushna, Teekshna, Sukshma, Vyavayi, and Vikashi Gunas are qualities of medications that produce Virechana Karma and are entirely or partially present in Virechana Dravyas. Though all Virechana medications are Panchabhautik, Pritvi and Aap Mahabhuta are dominating in their composition. All the drugs which possess Pritvi and Aap Mahabhuta cannot produce Virechana but the inherent property to move downwards are especially due to Adhobhagahara Prabhava of the drug.